In Search of Chaos in Genetic Systems - Felix Sadyrbaev; Olga Kozlovska (Chaos Theory and Applications)
A three-dimensional multiparametric system of ordinary differential equations, arising in the theory of genetic networks, is considered. The examples of chaotic behavior are constructed using the methodology by Shilnikov. This methodology requires the existence of a saddle-focus points satisfying some additional conditions. As the result, reach dynamical behavior of solutions can be observed, including chaotic behavior of solutions.